Graphitic Carbon Nitride Materials: Controllable Synthesis and Applications in Fuel Cells and Photocatalysis - Zheng, Y.; Liu, Jian; Liang, J.; Jaroniec, M.; Qiao, S. (Royal Society of Chemistry, 2012)
Graphitic carbon nitrides (g-C3N4) are becoming increasingly significant due to the theoretical prediction of their unusual properties and promising applications ranging from photocatalysis, heterogeneous catalysis, to fuel cells. Recently, a variety of nanostructured and nanoporous g-C3N4 materials have been developed for a wide range of new applications. This feature article gives, at first, an overview on the synthesis of g-C3N4 nanomaterials with controllable structure and morphology, and secondly, presents and categorizes applications of g-C3N4 as multifunctional metal-free catalysts for environmental protection, energy conversion and storage. A special emphasis is placed on the potential applications of nanostructured g-C3N4 in the areas of artificial photocatalysis for hydrogen production, oxygen reduction reaction (ORR) for fuel cells, and metal-free heterogeneous catalysis. Finally, this perspective highlights crucial issues that should be addressed in the future in the aforementioned exciting research areas.